A Study on the Current Situation and Countermeasures of Integrating Local Red Culture into Moral Education in Basic Education Schools: A Case Study of Tonghua Region - Wang, Han; Xu, Shuang; Jeong, Dubae (Journal of Educational Research and Policies, 2024)
Moral education constitutes a fundamental aspect of youth education, serving as its core essence. Red culture, representing revolutionary culture, is a crucial component of socialist advanced culture and encompasses a wealth of resources for moral education. Integrating red culture into youth moral education ensures that the spirit of red culture permeates the hearts of every student, enhances their ideological understanding, fosters patriotic sentiments, transmits the red gene, and promotes the dissemination of red culture.